ANALISIS PENATAAN ARSIP INAKTIF DI BIDANG ANGGARAN PADA BPKAD PROVINSI JAWA TENGAH - Winandia Dwi Rahmayani Putri; Yayuk Endang Irawati (Department of History Education, Faculty of Social Science, Universitas Negeri Medan, 2023)
Inactive archive management is the process of organizing and managing archives that are no longer actively used in the operational or administrative activities of an organization. The purpose of structuring inactive archives is to ensure that they are maintained, easily accessible if needed, and avoid damage or loss. In this case, it examines the arrangement of inactive archives in the budget sector at BPKAD Central Java Province. This study uses a qualitative method, descriptive approach using interviews and observations. In this study it was found that there was an inaccuracy in the arrangement of inactive archives at BPKAD Central Java Province where the archives were not neatly arranged, the lack of physical storage space and the weakness of human resources to manage archives became obstacles and challenges. So it can be concluded that there are obstacles in structuring inactive archives. However, there are efforts to increase human resources and improve facilities and infrastructure..